Peningkatan Pembelajaran Pancasila Terintegrasi Literasi Dan Numerasi Melalui Model Problem Based Learning Berbantuan Media Educaplay Di Kelas II SDN Tambakrejo 01 - Dewi Lestari, Marsela; Damayani, Aries Tika; Wijayanti, Arfilia; Ika Susianingsih (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2025)
This study aims to improve the learning outcomes of Pancasila Education integrated with literacy and numeracy through the application of the Problem Based Learning (PBL) model assisted by Educaplay digital media. The background of this study is based on the low literacy and numeracy skills of students at SDN Tambakrejo 01, which is reflected in the results of the initial assessment with literacy completeness of 25% and numeracy of 21%. The research used a Classroom Action Research (PTK) approach which was carried out in three cycles. Each cycle included planning, implementation, observation and reflection stages. Pre-cycle results showed that most students had not reached the Criteria for Achievement Level Completeness (KKTP). Through the application of PBL and the gradual use of Educaplay media, there was a significant increase in each cycle. In cycle I, literacy completeness reached 37% and numeracy 33%. Cycle II increased to 54% (literacy) and 46% (numeracy). Cycle III showed the success of learning with literacy and numeracy completeness of 75% each. This study concludes that the use of the PBL model supported by Educaplay interactive media is effective in increasing learner involvement and learning outcomes of Pancasila Education integrated with literacy and numeracy.